Effect of gatifloxacin against Mycoplasma genitalium-related urethritis: an open clinical trial. Issue 5 (28th April 2011) - Hamasuna, Ryoichi; Takahashi, Satoshi; Kiyota, Hiroshi; Yasuda, Mitsuru; Hayami, Hiroshi; Arakawa, Soichi; Tomono, Kazunori; Matsumoto, Tetsuro
Abstract : Objectives: Mycoplasma genitalium and Chlamydia trachomatis are the primary pathogens detected from non-gonococcal urethritis (NGU). In this study, the efficacy of gatifloxacin was examined against M genitalium -related urethritis. Methods: The study was an open clinical trial evaluating the effectiveness of gatifloxacin with 200 mg doses twice a day for 7 days against male NGU. Results: Between March and September 2008, 169 male patients were enrolled, and microbiological and clinical cure rates could be evaluated in 86 patients detected with C trachomatis or M genitalium and in 135 with NGU, respectively. Microbiological cure rates of gatifloxacin against C trachomatis and M genitalium were 100% and 83%, respectively, and the total clinical cure rate was 99%. Conclusion: Analysis of in-vivo and in-vitro data from the literature of fluoroquinolone efficacies against M genitalium suggests that a MIC90 of 0.125 μg/ml or less may be useful for optimal activity against M genitalium infection.